INVENTORY MANAGEMENT BASED ON THE KAIZEN METHODOLOGY: case study in a food industry - Casagrande, Diego José; Venção, Maísa Carolina (Revista Interface Tecnológica, 2023)
One of the most recognized process improvement philosophies is Kaizen. The effective implementation of Kaizen leads the organization to success. Inventory Control and Kaizen is part of the day-to-day of companies and is a subject that has several works published due to its importance. This is the reason for proposing this theme. The objective of this research is to make an analysis regarding inventory management based on the Kaizen methodology in a food industry. Having as a research method the Case Study in a food industry that uses Kaizen in its Distribution Center. It was analyzed that it is not possible to serve the customers that the industry has without the use of Kaizen in the storage environment due to the high complexity of the Distribution Center and to meet the requirements of its customers.